The Cambridge history of socialism: volume 1 - Linden, Marcel van der (Cambridge histories online, 2023)
This volume describes the various movements and thinkers who wanted social change without state intervention. It covers cases in Europe, the Americas, Africa and Asia. The first part discusses early egalitarian experiments and ideologies in Asia, Europe and the Islamic world, and then moves to early socialist thinkers in Britain, France, and Germany. The second part deals with the rise of the two main currents in socialist movements after 1848: anarchism in its multiple varieties, and Marxism. It also pays attention to organisational forms, including the International Working Men's Association (later called the First International); and it then follows the further development of anarchism and its 'proletarian' sibling, revolutionary syndicalism - its rise and decline from the 1870s until the 1940s on different continents. The volume concludes with critical essays on anarchist transnationalism and the recent revival of anarchism and syndicalism in several parts of the world.